Strengthening the global diagnostic capacity in the battle against Corona Virus - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Medicine Science, 2020)
The Corona Virus Disease-2019 (COVID-19) pandemic has taken the world by storm and since its emergence in the Wuhan city of China, the number of confirmed cases has been ever-rising. There is an immense need for the national leaders to prioritize COVID-19 and take targeted measures to improve diagnostic, case surveillance, infection prevention & control, treatment, risk communication and community engagement activities. From the diagnostic perspective, a significant improvement needs to be done as the dynamics of the outbreak is changing with each day. It has been envisaged that each of the nations should strengthen their capacity to detect the virus and not be dependent on other nations for the same as this will unnecessarily delay the diagnosis. In conclusion, amidst the reports of a rise in the number of asymptomatic cases and in the global battle against the COVID-19 outbreak, there is an indispensable need to strengthen serological testing and simultaneously improve the diagnostic capacity of the laboratories to ensure a better response against the disease. [Med-Science 2020; 9(4.000): 1102-3]